1997
DOI: 10.1093/nar/25.4.750
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and mitochondrial uracil-DNA glycosylases are generated by alternative splicing and transcription from different positions in the UNG gene

Abstract: A distinct nuclear form of human uracil-DNA glycosylase [UNG2, open reading frame (ORF) 313 amino acid residues] from the UNG gene has been identified. UNG2 differs from the previously known form (UNG1, ORF 304 amino acid residues) in the 44 amino acids of the N-terminal sequence, which is not necessary for catalytic activity. The rest of the sequence and the catalytic domain, altogether 269 amino acids, are identical. The alternative N-terminal sequence in UNG2 arises by splicing of a previously unrecognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
197
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(205 citation statements)
references
References 20 publications
6
197
0
2
Order By: Relevance
“…Burgers and Yoder [47] reported that PCNA could stimulate synthesis by DNA polymerase δ on linear templates by slipping onto the end of the DNA in an ATP-independent manner, although a large molar excess was required for maximal stimulation. Since large amounts (810 pmol) of PCNA were required in order to detect stimulation of UNG2 activity, was passive end-loading of PCNA onto the calf thymus [uracil- 3 810 pmol), and the amount of excised 3 H uracil was quantified as described under Section 2; the results are shown in Fig. 7A.…”
Section: Effect Of Rfc On Pcna-mediated Stimulation Of Ung2 Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Burgers and Yoder [47] reported that PCNA could stimulate synthesis by DNA polymerase δ on linear templates by slipping onto the end of the DNA in an ATP-independent manner, although a large molar excess was required for maximal stimulation. Since large amounts (810 pmol) of PCNA were required in order to detect stimulation of UNG2 activity, was passive end-loading of PCNA onto the calf thymus [uracil- 3 810 pmol), and the amount of excised 3 H uracil was quantified as described under Section 2; the results are shown in Fig. 7A.…”
Section: Effect Of Rfc On Pcna-mediated Stimulation Of Ung2 Activitymentioning
confidence: 99%
“…In human cells, the UNG gene encodes both the nuclear form (UNG2) and the mitochondrial pre-form (UNGl) of uracil-DNA glycosylase using different promoters and alternative splicing [3]. UNGl and UNG2 have unique N-terminal domains ☆ This work was supported by National Institute of General Medical Sciences Grant GM66245.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This activity, which excises uracil from DNA, was later named UDG1 when it was purified from human cells by affinity chromatography. It is a 30kd protein, encoded by the same gene which encodes the 36kd nuclear form of the protein (157,158).…”
Section: Mitochondrial Repair Proteinsmentioning
confidence: 99%